Does IGF-1 Shape Life-History Trade-Offs? Opposite Associations of IGF-1 With Telomere Length and Body Size in a Free-Living Bird - Montoya, Bibiana; Tóth, Zsófia; Lendvai, Ádám Z.; Stier, Antoine; Criscuolo, François; Zahn, Sandrine; Bize, Pierre (Frontiers in Ecology and Evolution, 2022)
Hormonal pathways have been proposed to be key at modulating how fast individuals grow and reproduce and how long they live (i.e. life history trajectory). Research in model species living under controlled environment is suggesting that insulin-like growth factor 1 (IGF-1), which is an evolutionarily conserved polypeptide hormone, has an important role in modulating animal life histories. Much remains however to be done to test the role played by IGF-1 in shaping the phenotype and life history of animals in the wild. Using a wild long-lived bird, the Alpine swift (Tachymarptis melba), we show that adults with higher levels of IGF-1 had longer wings and shorter telomeres. Hence, telomeres being a proxy of lifespan in this species, our results support a potential role of IGF-1 at shaping the life-history of wild birds and suggest that IGF-1 may influence lifespan.